An advanced geospatial assessment of the Levelised cost of energy (LCOE) for wave farms in Irish and western UK waters - O'Connell, Ross; Kamidelivand, Mitra; Furlong, Rebecca; Guerrini, Marco; Cullinane, Margaret; Murphy, Jimmy (Renewable energy, 2024)
With the climate crisis becoming an ever-growing concern, Europe is striving to reduce its energy related greenhouse gas emissions. On the western edge of this continent, wave energy is a logical future clean energy consideration for Ireland and the U.K. to help realise ambitious targets recently being set in policy. Yet to reach commercialisation, there is still much uncertainty surrounding the financial feasibility of wave farms in the region of interest, and where exactly the most feasible locations are likely to be. The Levelised Cost of Energy (LCOE) is the most commonly used metric in determining the financial feasibility of an energy project, and it is very much site dependant when it comes to wave energy, varying considerably from one location to the next. This study uses the geographic approach to address this and estimate the LCOE of wave energy farms in the region, considering different technology types and the geospatially variable inputs at play. The results reveal areas of high project feasibility in the Atlantic Ocean (off the west coast of Ireland), the Celtic Sea and the Inner Seas off the West Coast of Scotland (ISWCS), with LCOE values below 110€/MWh along the coasts of these areas.